Effects of water stress on secondary metabolism of Panax ginseng fresh roots. - Wei Zhang; Wenfei Liu; Liyang Wang; Pengcheng Yu; Xiaowen Song; Yao Yao; Xiubo Liu; Xiangcai Meng (PLoS ONE)
The roots and rhizomes of Panax ginseng C.A. Mey are commonly used herbal medicine in Asian countries. These components contain a large number of secondary metabolites known as ginsenosides, which serve as primary active ingredient. Environmental factors significantly influence the production of secondary metabolites, which are crucial for enhancing plant adaptability to ecological stress. P. ginseng is a shady plant that thrives in a constantly humid and temperate environment. However, it cannot withstand excessive moisture, making soil moisture a significant ecological stress affecting P. ginseng survival. In this study, we applied a water spray to maintain a water-saturated surface on 5-year-old fresh P. ginseng roots for a duration of 5 days, to establish a short-term water stress condition. The results revealed a notable increase in superoxide anion (O2·-), hydrogen peroxide (H2O2), and NADPH oxidase (NOX) activity (p < 0.01), as well as malondialdehyde (MDA) contents (p < 0.01) in both the main root and fibrous root of P. ginseng. Additionally, superoxide dismutase (SOD), catalase (CAT), peroxides (POD), ascorbate peroxidase (APX) and glutathione reductase (GR) activities also elevated significantly under water stress (p < 0.01). Ascorbic acid (AsA), glutathione (GSH) and oxidized glutathione (GSSG) contents also showed a marked increase (p < 0.01). The main root treated with water showed the most positive impact on the 5th day. Water stress boosted the activities of key enzymes including 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR), farnesyl pyrophosphate synthase (FPS), squalene synthase (SS), squalene epoxidase (SE), and dammarenediol-II synthase (DS) involved in the ginsenoside biosynthesis pathway (p <0.01). This resulted in a significant an increase in the level of ginsenosides Rg1, Rb1, Rf, Rg2+Rh1, Rc, and Rb3, by 42.4%, 21.0%, 15.7%, 157.9%, 18.3%, and 10.6% respectively, and an increase of 40.1% in total saponins content. Similarly, the fibrous root changes in the treated sample showed the most positive impact on the 4th day. Specifically, Rg1, Re, Rb1, Rf, Rg2+Rh1, Rc, Ro, and Rb2 increased by 41.8%, 20.5%, 17.3%, 84.3%, 30.7%, 35.6%, 8.6%, and 7.6%, respectively, and an increase of 4.2% in total saponins content. Furthermore, 1,3-disphosphoglycerate (1,3-DPG) contents and phosphoenolpyruvate carboxylase (PEPC) activities, which are key intermediate of primary metabolism, were significantly elevated under water stress (p < 0.01). This indicates that the primary source of the raw materials used in the biosynthesis of secondary metabolites is sugars. Pharmacodynamic analysis demonstrated that water stress could increase the contents of ginsenosides, improve the quality of ginseng, and enhance the efficacy of ginseng root to a certain extent.